The role of the tutor in project-led education : the developement of an evaluation instrument - Hattum-Janssen, Natascha van (2008)
Project-led education as implemented at a number of engineering courses of the University of Minho requires an approach to learning in which part of the teaching staff is not mainly teaching, but act as facilitators of learning. While tutoring groups of students working on a project, tutors try to guide students towards a working solution, also paying attention to the acquisition of specific technical and non-technical competencies meanwhile. The differences between the role of a teacher and that of a tutor may create some ambiguity both for students as well as teachers. A study on the evaluation of teachers acting as tutors was carried out in de second semester of the academic year 2006/2007 to identify expectations and opinions of students towards their tutors. Knowledge on project-led education, attitudes towards groups, progress of the project, development of critical thinking, group functioning, individual learning and assessment were topics included in the evaluation.